Новый вид рода Mallomonas Perty (Synurales, Chrysophyceae) из водоёмов Вьетнама - Гусев, Е.С. (Альгология, 2015)
Описан новый вид – Mallomonas paragrandis E.S. Gusev sp. nov. (род Mallomonas) из водоёмов Вьетнама. По морфологическому строению чешуек он относится к секции Planae и наиболее сходен с таксонами комплекса M. matvienkoae Asmund & Kristiansen, в частности с M. sorohexareticulata Jo, Shin, Kim, Siver & Andersen, M. hexareticulata Jo, Shin, Kim, Siver & Andersen и M. matvienkoae var. grandis Dürrschmidt & G. Cronberg. Молекулярно-генетический анализ на основе трех генов (ядерные 18S, 28S рДНК и пластидный rbcL) также показал, что M. paragrandis находится в одной кладе с таксонами комплекса M. matvienkoae и подтвердил обоснованность выделения нового вида. Mallomonas paragrandis E.S. Gusev sp. nov. is described from Zua River, located in Khanh Hoa Province, Central Viet Nam. The description is based on silica-scale morphology studied by means of transmission and scanning electron microscopy. New species has oval or obovoid scales with evenly distributed large pores in proximal half of the scales. Distal part is covered with hexagonal reticulation with minute pores inside each mesh and papillae in the angles of the meshes. New species belongs to the Section Planae and closely related to Mallomonas sorohexareticulata Jo, Shin, Kim, Siver & Andersen, M. hexareticulata Jo, Shin, Kim, Siver & Andersen and M. matvienkoae Asmund & Kristiansen var. grandis Dürrschmidt & G. Cronberg. Results of morphological comparison were approved by molecular analysis on the basis of nuclear 18S and 28S rDNA and plastid rbcL genes.